2019
DOI: 10.1016/j.media.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Training recurrent neural networks robust to incomplete data: Application to Alzheimer’s disease progression modeling

Abstract: Disease progression modeling (DPM) using longitudinal data is a challenging machine learning task. Existing DPM algorithms neglect temporal dependencies among measurements, make parametric assumptions about biomarker trajectories, do not model multiple biomarkers jointly, and need an alignment of subjects' trajectories. In this paper, recurrent neural networks (RNNs) are utilized to address these issues. However, in many cases, longitudinal cohorts contain incomplete data, which hinders the application of stan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Functional connectivity analysis found decreased connectivity in the superior temporal gyrus in dementia patients including AD (Hafkemeijer et al, 2015; Schwab et al, 2018). The middle temporal gyrus has been shown to atrophy significantly in both MCI and AD patients when compared to controls in longitudinal studies (Ghazi et al, 2019) and research that combined multi-modal data types (Convit et al, 2000; Korolev et al, 2016). Finally, Guo et al found significant gray matter volume reductions in the superior and middle temporal gyrus (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Functional connectivity analysis found decreased connectivity in the superior temporal gyrus in dementia patients including AD (Hafkemeijer et al, 2015; Schwab et al, 2018). The middle temporal gyrus has been shown to atrophy significantly in both MCI and AD patients when compared to controls in longitudinal studies (Ghazi et al, 2019) and research that combined multi-modal data types (Convit et al, 2000; Korolev et al, 2016). Finally, Guo et al found significant gray matter volume reductions in the superior and middle temporal gyrus (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we considered recurrent neural networks (RNNs), which allow an individual's latent state to be represented by a vector of numbers, thus providing a richer encoding of an individual's "disease state" beyond a single integer (as in the case of discrete state hidden Markov models). In the context of medical applications, RNNs have been used to model electronic health records (Lipton et al, 2016a;Choi et al, 2016;Esteban et al, 2016;Pham et al, 2017;Rajkomar et al, 2018;Suo et al, 2018) and AD disease progression (Nguyen et al, 2018;Ghazi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other models are also based on differential equation models [3]. Non parametric models using deep learning were also explored [16].…”
Section: Related Workmentioning
confidence: 99%